Knowledge, Attitudes, and Practices Associated With Diabetic Foot Prevention Among Rural Adults With Diabetes in North China - Jia, Huimin; Wang, Xiaocheng; Cheng, Jingmin (Frontiers in Public Health, 2022)
Background: The diabetic foot is a worldwide threat to public health as it can lead to infection, amputation, and it is the cause of great suffering and financial costs to the patient. Compared to the south, the diabetic foot in northern China is characterized by more severe local ulcers, poorer prognosis and a longer duration of disease. The diabetic foot can be effectively avoided through appropriate preventive measures. This study assesses the existing knowledge, attitudes and practices related to diabetic foot prevention among adults with diabetes living in rural areas of northern China. Method: This cross-sectional survey included 1080 rural adults of northern China; cluster sampled 12 villages and surveyed diabetic patients without diabetic foot who participated in community diabetes management. The self-administered Knowledge and Attitude Questionnaire and Chinese version of the Nottingham Assessment of Functional Foot-care Questionnaire (CNAFF) were used. Result: Of the 1080 subjects, 51.6% received moderate knowledge scores, 63.9% had a positive attitude and 71.4% received poor practice scores. In terms of knowledge, parameters such as knowledge about foot examinations and treatment of foot problems scored the lowest. In terms of practice, in line with the results of the low knowledge score, parameters such as the pursuit of medical treatment for foot problems and routine foot examinations were associated with the lowest scores. Multiple regression analysis revealed that participants never smoke had higher knowledge scores; participants who had never smoked and had higher knowledge scores achieved higher scores on attitudes; gender, duration of diabetes, knowledge and attitudes were significantly associated with practice. Conclusions: Increasing knowledge regarding diabetic foot would help instil positive attitudes and cultivate better practices towards diabetic foot prevention. The results of this study may help guide future promotional resources to those groups most in need, which may help lower the occurrence of diabetic foot among adults in northern China.